Self-Control at Work - Kaur, Supreet; Kremer, Michael; Mullainathan, Sendhil (Journal of Political Economy, 2015)
Self-control problems change the logic of agency theory by partly aligning the interests of the firm and worker: both now value contracts that elicit future effort. Findings from a year-long field experiment with full-time data entry workers support this idea. First, workers increase output by voluntarily choosing dominated contracts (which penalize low output but give no additional rewards for high output). Second, effort increases closer to (randomly assigned) paydays. Third, the contract and payday effects are strongly correlated within workers, and this correlation grows with experience. We suggest that workplace features such as high-powered incentives or effort monitoring may provide self-control benefits.